Performance and Efficiency Analysis of NTFS, exFAT, and EXT4 on SSD Using a Multi-Workload Approach - Wahyudin Wahyudin; Agung Permana; Jan Everhard (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
The increasing adoption of Solid State Drives (SSDs) as primary storage media requires careful selection of file systems that can deliver optimal performance and efficiency. Although numerous studies have compared file system performance, most focus on only two file systems or employ limited testing scenarios. This study evaluated the performance and efficiency of NTFS, exFAT, and EXT4 file systems on SSD using a multi-workload benchmarking approach in an Ubuntu Server 22.04 environment running on Oracle VirtualBox. Testing was conducted across five workload scenarios: Sequential Read, Sequential Write, Random Read, Random Write, and Small File Management, with throughput, latency, IOPS, CPU utilization, and storage overhead as measured parameters. Each scenario was repeated three times and analyzed using descriptive statistics. Results indicated that exFAT tended to produce higher throughput on sequential workloads (544 MB/s on Sequential Read; 495 MB/s on Sequential Write), although differences with EXT4 were marginal. EXT4 showed clearer advantages on random workloads (44,700 IOPS on Random Read; 34,500 IOPS on Random Write) and achieved the fastest completion time of 101.2 seconds on Small File Management. exFAT recorded the lowest storage overhead (0.2%) and CPU utilization (4.6%). The study concluded that no single file system outperformed all others across every workload; therefore, file system selection should be aligned with the dominant workload characteristics of the target system.